PENGARUH ETOS KERJA, KEPUASAN KERJA, SIKAP KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN POLONIA - Putra Arif Simanjuntak (Manajemen dan Bisnis, 2020)
The problems in this research are: How the influence of work ethic on employee performance at the Medan Polonia Tax Service Office, How the influence of job satisfaction on employee performance, How does the influence of work attitudes on employee performance, How does work motivation influence employee performance, How does work ethic influence, job satisfaction, work attitude and work motivation on employee performance at the Medan Polonia Primary Tax Service Office. The hypothesis proposed is: Work ethic has a positive and significant effect on employee performance at the Medan Polonia Tax Service Office, Job satisfaction has a positive and not significant effect on employee performance, work attitude has a positive and not significant effect on employee performance, work motivation has a positive and significant effect on employee performance, work ethic, job satisfaction, work attitude and work motivation have a positive and significant effect on employee performance at the Medan Polonia Tax Office. The study was conducted at the Medan Polonia Tax Office. Jalan Sukamulia No. 17-A, Medan-20151 with 92 research samples. Based on the analysis results obtained value of work ethic t = 2,900, while t-table with dk 92 (Appendix) of 1.66, then t count t-table thus partially there is a significant influence between work ethic on employee performance. Value of t Job satisfaction = 1.838, while t-table with dk 92 (Appendix) of 1.66, then t count t table thus partially there is a significant influence between Job satisfaction on employee performance, Value of t Attitude of work = 1,785, while t-table with dk 92 (Appendix) of 1.66, then t count t table thus partially there is a significant influence between work attitude on employee performance, t value of work motivation = 2.164, while t-table with dk 92 (Attachment ) equal to 1.66 then t arithmetic t table thus partially there is a significant influence between work motives on employee performance, F-calculated value of 110.718 while the value of F-table (Appendix) with the numerator dk 4 and the denominator 87 is equal to 2.48 where F-count F table (110.718 2.48) it can be stated that together (multiple) there is a positive and significant influence on work ethics, job satisfaction, work attitude and motivation on employee performance wai